PENGARUH MOTIVASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN DI KANTOR KOPERASI SIMPAN PINJAM SEJAHTERA KECAMATAN TIKALA KOTA MANADO - Umaternate, Arfia; Rompas, Sonny; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
This research aims to to know how to influence the motivation of work (external and Internal) in the Office of Cooperative Peace Subdistrict Tikala then to know the motivations which are the most influential in the labor productivity of the employees at the Office of Cooperative Peace Tikala Subdistrict. Given the importance of motivation, then a form of management’s attention on the issue of employee motivation in working is to do business with the way giving motivation in employees in certain business through a series of cooperative in accordance with the policy of the cooperative, so the motivation of employees in work will be maintained. To motivate employees, cooperative leader should know the motives and motivations that are desired by those employees increased productivity is essentially a process terminating an alloy of various interests. The methods used in this research is quantitative methods. With the technique of gathering research library and field research. In the study which became population is thriving, Cooperative Office employee at Sub Tikala totalling 54 people. That becomes the variable X (Motivation) and becomes the variable Y (Motivational performance). From the results of the analysis, the results obtained that external motivation (working conditions, a good Boss, Financial and social Assurance) gives influence in the improved productivity performance of the cooperative. While the analysis obtained from internal motivation (a job that is fun, challenging Work, and interesting work) exert influence in increasing productivity. External and internal motivation effect simultaneously on performance of employees. This is proven by the regression coefficient of external motivation is greater than internal motivation. The influence of motivation in organization of higher employee to productivity, so as to enhance cooperative targets set. Then recommend to the company in order to maximize internal motivation. Because when the external and internal motivation is given with a balanced employee then it is definitely on the rise. The company should pay more attention to external motivation on communication between the employee and the employer, when an employee feels comfortable with the automatic communication of their work productivity increased. A leader should pay attention to the rights of employees who perform by giving rewards to motivate employees, satisfying the needs of individuals in the organization. Employee motivation should be heeded by the leadership, so that the specified targets or in the expected by the company can be accomplished according to demands of the company. Keys words: Motivation, increased work productivity